2022
DOI: 10.1080/10717544.2022.2118400
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the oral bioavailability of isopropoxy benzene guanidine though complexation with hydroxypropyl-β-cyclodextrin

Abstract: Isopropoxy benzene guanidine (IBG) is a novel substituted benzene guanidine analogue with antibacterial activity against multidrug-resistant bacteria. However, the bioavailability of IBG is not optimal due to its finite aqueous solubility, thus hampering its potential therapeutic exploitation. In this study, we prepared IBG/hydroxypropyl-β-CD (IBG/HP-β-CD) complex, and characterized it by differential scanning calorimetry, Fourier transform infrared spectroscopy, powder X-ray diffraction, and scanning electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…The BS diagram indicates an initial increase in apparent solubility, followed by a plateau evolution and the diagram is B I if the complex formed is insoluble. 28 The diagram o β-CD appears linear or concentrations below 10 mM. Our result is similar to that of Savic et al who found an AL-type diagrams with β-CD and HP β-CD.…”
Section: Study Of Phase Solubilitysupporting
confidence: 92%
“…The BS diagram indicates an initial increase in apparent solubility, followed by a plateau evolution and the diagram is B I if the complex formed is insoluble. 28 The diagram o β-CD appears linear or concentrations below 10 mM. Our result is similar to that of Savic et al who found an AL-type diagrams with β-CD and HP β-CD.…”
Section: Study Of Phase Solubilitysupporting
confidence: 92%
“…α-CD and γ-CD exhibited a series of strong and sharp diffraction peaks, indicating that these two natural CDs existed in crystalline form ( Figure 3 A,C). In contrast, HP-β-CD was amorphous, displaying a diffuse halo pattern, as shown in Figure 3 B [ 38 ]. In the diffraction patterns of three CRT/CD PMs, peaks derived from the CRT crystal and three natural CDs were observed, which could be a simple superposition of the drug and each CD.…”
Section: Resultsmentioning
confidence: 99%